Identification of Aluminum Tolerance in Ethiopian Chickpea (Cicer arietinum L.) Germplasm - Hawi Negusse; Douglas R. Cook; Teklehaimanot Haileselassie; Kassahun Tesfaye (Agronomy, 2022)
Aluminum (Al) toxicity is a major abiotic stress that negatively impacts plant growth and crop productivity. Al ions are released into soil solutions as a function of soil pH, which is in turn determined by a combination of factors, including local geology, historic vegetation and land-use patterns. Selection and use of Al-tolerant crops is a preferred method to address the problem of Al toxicity. The present study evaluated a combination of modern cultivars, advanced breeding lines and a local landrace for Al tolerance using a seedling-based hydroponic assay. Two sequential experiments were conducted to score root and shoot traits in the presence of aluminum. Initially, six Al concentrations (0, 50, 100, 120, 150 and 200 µM) were tested on six chickpea genotypes to identify the single Al concentration that best discriminates among genotypes. Subsequently, 31 chickpea genotypes were evaluated at 0 and 120 µM Al. Progressive declines in trait values were observed in all genotypes with increasing Al, although the degree of sensitivity varied significantly among genotypes. Genotypes were evaluated both for total root length under 120 µM Al and for relative root growth compared to a 0 µM Al control treatment. Considering both parameters, we identified four tolerant chickpea genotypes (DZ-2012-CK-0237, Wollega LV, DZ-2012-CK-0233 and Natoli) and two sensitive genotypes (Akaki and Fetenech). Wollega LV is a local landrace obtained from acidic soil regions of Western Ethiopia, presenting the possibility that historical selection during cultivation on acidic soils might underlie its unusual tolerance. The aluminum tolerance traits identified here are candidates for introgression breeding of new Ethiopian chickpea varieties with potential to increase yield and expand the area of cultivation.